Gamma-glutamyl transpeptidase and indirect bilirubin may participate in systemic inflammation of patients with psoriatic arthritis - Xu Wang; Yan Mao; Shang Ji; Huanrong Hu; Qian Li; Lichao Liu; Shaomin Shi; Yaling Liu (Advances in Rheumatology, 2023)
Abstract Background Previous studies have suggested that systemic metabolic abnormalities are closely related to psoriatic arthritis (PsA). Gamma-glutamyl transpeptidase (GGT) and indirect bilirubin (IBIL), two essential active substances in hepatic metabolism that have been demonstrated as an oxidative and anti-oxidative factor respectively, have been proved to be involved in oxidative stress damage and inflammation in several human diseases. However, their role in PsA remains unclear. Methods In this retrospective comparative cohort study, a case group of 68 PsA patients and a control group of 73 healthy volunteers from the Third Hospital of Hebei Medical University were enrolled. Serum GGT, IBIL, GGT/IBIL ratio and C-reactive protein (CRP), a well applied bio-marker of systemic inflammatory in PsA, were compared between the two groups. Furthermore, the relationship of GGT, IBIL and GGT/IBIL with CRP were explored in PsA patients. Finally, the patients were divided into high inflammation group and low inflammation group according to the median value of CRP. Multivariate logistic regression analyses were used for the association of systemic inflammation level with GGT, IBIL and GGT/IBIL. Results Compared with healthy controls, PsA patients exhibited significantly higher serum GGT, GGT/IBIL, and CRP levels and lower IBIL levels. Serum GGT and GGT/IBIL were positively correlated with CRP, whereas IBIL were negatively correlated with CRP. Binary logistic regression analysis revealed that serum GGT was a risk factor for high CRP in PsA, whereas IBIL was a protective factor. Furthermore, GGT/IBIL was a better indicator of high CRP condition in PsA patients than either GGT or IBIL alone, as determined by the receiver operating characteristic curves. Conclusion GGT and IBIL may participate in the pathogenesis of PsA. Additionally, GGT, IBIL and the balance of the two may reflect systemic inflammation mediated by oxidative stress events related to metabolic abnormalities to a certain extent.